International community service collaboration: Recommendations for village asset management in Kedah, Malaysia - Dita Fisdian Adni; Tessa Shasrini; Farahiyah Fadzil (Universitas Muhammadiyah Malang, 2024)
Village assets consist of various forms, such as buildings, roads, and so on. Asset management by the village government in a professional, transparent, accountable, efficient and effective manner is very important. Properly managed village assets will produce benefits such as creating jobs, realizing sustainable development and ultimately positively impacting the economy. But in reality, there are many similarities in the problems of managing village assets in Indonesia and Malaysia, one of which is the problem of managing village assets so far is only limited to recording. Not yet to the management that can generate village income. This service activity aims to increase the understanding of the government apparatus of Singkir Darat Village, Kedah State, Malaysia, about managing village assets in a professional, transparent, accountable, efficient and effective manner. The method of implementing this service involves counseling, which includes planning, implementation, and monitoring in collaboration with Universiti Utara Malaysia. The instrument for evaluating this activity is a questionnaire, and then analyzed descriptively. The results of this service show an increase in the understanding of the Singkir Darat Village Government apparatus and the community about the importance of village asset management, asset inventory and innovation in village asset management. Through this activity, the management of assets owned by Singkir Darat village can be carried out optimally to realize quality services to the community.